DAMPAK WISATA RELIGI MASJID RAYA BAITURRAHMAN TERHADAP PENDAPATAN PEDAGANG SEBELUM DAN SEMASA COVID 19 KOTA BANDA ACEH - Erwin Kurniawan Lubis; Fikriah Fikriah (Fakultas Ekonomi dan Bisnis UNSYIAH, 2023)
ABSTRACTThis study aims to analyze the impact of the religious tourism object of the Baiturrahman GreatMosq ue on the income of local traders before and d uring the Covid 19 pandemic. The analysisused is quantitative using the chi square test method with crosstab as well as a comparativeanalysis of the income of traders around before and during the Covid 19 pan demic using thepaired simp le t test method . The results of the study show that each test variable in theBaiturrahman Gre at Mosque Religious Tourism has a positive relationship to merchant income asevidenced by the chi square significance results in the pre pandemic period, there were 2insignificant variables while during the pandemic there were 4 insignific ant variables. This resultshows acceptance of the hypothesis that there is a significant relationship between religioustourism and merchant income. Comparison of the income level of traders before and during thecovid pandemic shows a change in the incom e level of traders. This research is limited to samplesselected by the criteria for the type of merchandise i n the form of clothing, souvenirs and f ood, itis hoped that further researchers can expand the study with samples for traders with other types ofmerchandiseKEYWORDS: Religious Tourism, Baiturrahman Grand Mosque, Business Activity Income.